2014
DOI: 10.1515/cog-2014-0061
|View full text |Cite
|
Sign up to set email alerts
|

Manners of human gait: a crosslinguistic event-naming study

Abstract: Crosslinguistic studies of expressions of motion events have found that Talmy's binary typology of verb-framed and satellite-framed languages is reflected in language use. In particular, Manner of motion is relatively more elaborated in satellite-framed languages (e.g., in narrative, picture description, conversation, translation). The present research builds on previous controlled studies of the domain of human motion by eliciting descriptions of a wide range of manners of walking and running filmed in natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 39 publications
2
47
1
1
Order By: Relevance
“…general purpose verbs such as say and tell than Spanish does. This is in stark contrast to the findings in Slobin et al (2014), who report the opposite pattern for verbs for motion in Spanish and English. In their data, based on a naming task, common core verbs such as go/ir, walk/andar and run/correr are far more common in Spanish than in English.…”
Section: Summary and Analysis Of The Resultscontrasting
confidence: 99%
“…general purpose verbs such as say and tell than Spanish does. This is in stark contrast to the findings in Slobin et al (2014), who report the opposite pattern for verbs for motion in Spanish and English. In their data, based on a naming task, common core verbs such as go/ir, walk/andar and run/correr are far more common in Spanish than in English.…”
Section: Summary and Analysis Of The Resultscontrasting
confidence: 99%
“…It is not surprising to find that a language spoken in a culture lacking cars does not have the words "sedan" and "hatchback" as part of its core vocabulary. But substantially different patterns of naming are also found across much more fundamental domains including spatial relations (Haun, Rapold, Janzen, & Levinson, 2011;Levinson & Wilkins, 2006), time (Boroditsky, Fuhrman, & McCormick, 2011;Boroditsky & Gaby, 2010), common actions (Majid, Bowerman, van Staden, & Boster, 2007;Slobin, Ibarretxe-Antunanõ, Kopecka, & Majid, 2014), kin relations (Kemp & Regier, 2012;Murdock, 1970), body parts (Enfield, Majid, & van Staden, 2006), basic shapes (Luria, 1976;Roberson, Davidoff, & Shapiro, 2002), and colors (Gibson et al, 2017;Majid et al, 2018;Roberson, Davidoff, Davies, & Shapiro, 2005;Steels & Belpaeme, 2005).…”
Section: The Role Of Natural Language In Categorizationmentioning
confidence: 99%
“…This has been shown for domains such as colors, emotions, artifacts, and topological relations (for recent reviews, see, e.g., Evans, ; Malt & Majid, ). Recently, research targeting semantic typology has turned its attention to event categorization, that is, the linguistic encoding of everyday events, such as carrying events (e.g., Bowerman, ; Saji et al., ), motion events (e.g., Malt et al., , ; Slobin, Ibarretxe‐Antuñano, Kopecka, & Majid, ), and cutting and breaking events (Majid, Gullberg, van Staden, & Bowerman, ; Majid, Boster, & Bowerman, ). The results of these studies have revealed cross‐linguistic differences in the number of semantic categories that are established and in their exact boundaries (i.e., how the events are grouped together).…”
Section: Introductionmentioning
confidence: 99%